'A glorious time?' Some reflections on flooding in the Somerset Levels. Issue 4 (December 2014) - McEwen, Lindsey; Jones, Owain; Robertson, Iain
<x xml:space="preserve">Abstract</x> Severe floods on the Somerset Levels in winter 2014, and a series of other recent extreme floods across the UK, pose questions about the research needed to unravel the complex nature of flood risk and its implications for society. While much emphasis is placed on research in the natural and engineering sciences to better predict flood risk and develop solutions, this paper discusses what social science, and arts and humanities approaches can contribute to this challenging issue, alongside, and importantly integrated with, the natural sciences. Drawing upon a series of interconnected social science and arts and humanities research projects, in this paper we explore how different knowledges might contribute in dialogue around flood risk; water, senses of place and community in resilience building; the power dynamics in narratives about water; and the value of conceptualising flood heritage 'from below' in bringing community voices to the table. We argue that social science, and arts and humanities approaches are needed to explore creative solutions to changing or challenging flood risk. In interdisciplinary configurations in particular, they can generate much needed, creative, transformative narratives which can play key roles in the interplay and negotiation between science, policy and public understanding.